Loss-Chasing, Alexithymia, and Impulsivity in a Gambling Task: Alexithymia as a Precursor to Loss-Chasing Behavior When Gambling - Bibby, Peter A. (Frontiers in Psychology, 2016)
Objective: To examine the relationship between loss-chasing, the propensity to continue gambling to recover from losses, alexithymia, a personality trait associated poor emotional processing and impulsivity, the tendency to act quickly without reflection or consideration of the consequences. Method: Two experiments are reported (E1: N=60, Males, 11; Age, 21.6 years. E2: N=49, Males, 22; Age, 21.1 years). In experiment 1, two groups (low alexithymia, high alexithymia) completed the Cambridge Gambling Task. Loss-chasing behaviour was investigated. In experiment 2, both alexithymia (low, high) and impulsivity (low, high) were examined also using the CGT. A further change was the order of bet proportion from ascending to descending. Results: Experiment 1 shows loss-chasing behaviour in participants high in alexithymia but not those low in alexithymia (η_p^2=.09). Experiment 2 shows loss-chasing behaviour in participants both low and high in alexithymia but it was greater for participants high in alexithymia (η_p^2=.09). The effect of impulsivity was not statistically significant (η_p^2=.01). Loss-chasing behaviour was correlated with the emotional facets of alexithymia but not the cognitive facet. Conclusions: Alexithymia is a precursor to loss-chasing when gambling and loss-chasing reflects the cognitive and emotional aspects of gambling. Specifically, the tendency to loss-chase depends on the need to recoup previous losses and failure to process the emotional consequences of those losses.